Ontological justification of the idea of progress - Smirnov, Victor E. (Journal of the Belarusian State University. Sociology, 2020)
One of the directions of ontological substantiation of the idea of progress is presented, which concerns the relationship between man and nature and the ability of man to transform it into a second nature in order to ensure a comfortable and safe life on the planet. The article presents a critique of modern approaches to the interpretation of the idea of progress, as well as justifies its objective necessity, both in knowledge and for implementation in practice. The author criticizes the old argument that imputes to the idea of progress the idea of the unchangeable direction of progressive changes, arguing that the traditional modern ideas about it have never been straightforward, since they included in the understanding of progress both forward movement and backward movement that is regression. In addition, it is shown that this idea of progress still determines the strategy of historical science today: the very fact that modern historical science rejects the idea of the so-called «dark ages», interpreted in terms of regression, indicates the ambiguous and concrete historical nature of the corresponding assessments. The article offers an understanding of progress in its ontology as a way and form of spiritual and practical relations between man and nature. Existing speculations on this issue are criticized, in particular, proclaiming the connection of the idea of progress with its ideologically coloured fault in nature pollution, global warming or cooling, ozone holes, stopping the Gulf stream. The author substantiates the idea that humanity is no longer able to exist outside of progressive development and under the influence of the idea of progress, and has a unique ideological embodiment in each historical epoch. Answering the question that concerns humanity, whether progress leads to the deterioration of the environment, the death of ecology and the destruction of the noosphere, or improves it, changes it in accordance with human needs, and who is man – the conqueror of nature or the Creator of a new, socio-natural reality, the author analyzes and justifies the objectively determined and vitally rooted ability of humanity to long projects, seeing them as a trigger for social progress. It is argued that human development occurs simultaneously with the creation of a second nature and social relations as an environment that provides local comfort zones in order to survive in a hostile natural environment. The current interpretation of the environment – nature, from the material of which a person builds a second nature – the humanized world, is criticized as exceptionally friendly, so much so that the line between the first nature and the second, humanized nature is significantly blurred. As a result, it was the second one that was often perceived as the first. According to this «ecological» vision, the idea was formed that it is man who aggressively breaks into nature, it is he who is hostile to it, destroying the environment of his habitat. The author warns that we must not forget that nature is also not kind to man: she is indifferent to him and ruthless, and therefore can be both cruel and hostile. The author warns that one must not forget that nature is also not kind to man: she is indifferent to him and ruthless, and therefore can be cruel and hostile. And it is this lesson that the latest pandemic, COVID-19, taught humanity. Using the example of the historical past and the present, it is shown that the desire of humanity, albeit unconscious, for long projects is the essence of human community, the basis of sociality and the creation of conditions for the preservation of man as a species. Various social spheres are analyzed as the results of the implementation of long-term projects on the path of progressive development.